Phosphorylation of a reinitiation supporting protein, RISP, determines its function in translation reinitiation. Issue 12 (16th June 2021) - Mancera-Martínez, Eder; Dong, Yihan; Makarian, Joelle; Srour, Ola; Thiébeauld, Odon; Jamsheer, Muhammed; Chicher, Johana; Hammann, Philippe; Schepetilnikov, Mikhail; Ryabova, Lyubov A
Abstract: Reinitiation supporting protein, RISP, interacts with 60S (60S ribosomal subunit) and eIF3 (eukaryotic initiation factor 3) in plants. TOR (target-of-rapamycin) mediates RISP phosphorylation at residue Ser267, favoring its binding to eL24 (60S ribosomal protein L24). In a viral context, RISP, when phosphorylated, binds the CaMV transactivator/ viroplasmin, TAV, to assist in an exceptional mechanism of reinitiation after long ORF translation. Moreover, we show here that RISP interacts with eIF2 via eIF2β and TOR downstream target 40S ribosomal protein eS6. A RISP phosphorylation knockout, RISP-S267A, binds preferentially eIF2β, and both form a ternary complex with eIF3a in vitro . Accordingly, transient overexpression in plant protoplasts of RISP-S267A, but not a RISP phosphorylation mimic, RISP-S267D, favors translation initiation. In contrast, RISP-S267D preferentially binds eS6, and, when bound to the C-terminus of eS6, can capture 60S in a highly specific manner in vitro, suggesting that it mediates 60S loading during reinitiation. Indeed, eS6-deficient plants are highly resistant to CaMV due to their reduced reinitiation capacity. Strikingly, an eS6 phosphomimic, when stably expressed in eS6-deficient plants, can fully restore the reinitiation deficiency of these plants in cellular and viral contexts. These results suggest that RISP function in translation (re)initiation is regulated by phosphorylation at Ser267.